THE THE EFFECT OF PRODUCT, WEBSITE QUALITY, CONSUMER’S TRUST, AND QUALITY OF DELIVERY AGAINST ON-LINE PURCHASING DECISION - Nur Hanifa; Parlagutan Silitonga (Panorama Nusantara, 2016)
The aim of this study is to findout the main factors effecting making decision to purchase goods via on-line shop. The sample used as respondents are the student of STIE Pariwisata Internasional (STEIN), Jakarta, using Slovin formula to decide the number of respondent, but respondents selection by accidental sampling. The data analyzed by multiple regression analysis using SPSS-version 20. The finding of this survey covering that the product quality as the main factor to purchase at on-line shop. This variable also followed by delivery quality, website quality and price. There are four major player that used by respondent such as Lazada, OLX, Kaskus, and Berniaga. However, Lazada is the most popular in the mind of respondent due to product quality and delivery.